2020
DOI: 10.15252/msb.20209442
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput, microscope‐based sorting to dissect cellular heterogeneity

Abstract: Microscopy is a powerful tool for characterizing complex cellular phenotypes, but linking these phenotypes to genotype or RNA expression at scale remains challenging. Here, we present Visual Cell Sorting, a method that physically separates hundreds of thousands of live cells based on their visual phenotype. Automated imaging and phenotypic analysis directs selective illumination of Dendra2, a photoconvertible fluorescent protein expressed in live cells; these photoactivated cells are then isolated using fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 65 publications
1
53
1
Order By: Relevance
“…Single cell tools already exist for addressing these issues by assaying chromatin accessibility ( Farmer et al, 2020 ) and mapping the epigenomic landscape of the cell ( Zhou et al, 2019 ). For understanding functional differences between paralogs, and for even finer scale “sub-localization” of gene action within cells that may be a driver of paralog retention ( Qiu et al, 2019 ), a host of other single cell-omics tools exist or are under development ( Macaulay et al, 2017 ; Hasle et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Single cell tools already exist for addressing these issues by assaying chromatin accessibility ( Farmer et al, 2020 ) and mapping the epigenomic landscape of the cell ( Zhou et al, 2019 ). For understanding functional differences between paralogs, and for even finer scale “sub-localization” of gene action within cells that may be a driver of paralog retention ( Qiu et al, 2019 ), a host of other single cell-omics tools exist or are under development ( Macaulay et al, 2017 ; Hasle et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter would enable SPOTlight to be combined with assays such as antibody staining that are often more easily performed outside of the microscope stage. While our manuscript was under revision, a study reported the application of a green-to-red photoconvertible protein for tagging and retrieving individual cells (43). Compared with our focus on a temporal property (photostability), the authors applied their method to spatial characteristics such as morphology and subcellular localization, demonstrating that our conceptual approach can be extended to a wide range of visual phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar strategy was independently developed by another group, highlighting the broad applicability and power of this approach toward identifying key regulators of previously intractable phenotypes 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many important cellular phenotypes can only be detected under a microscope, which requires a robust method for transforming optically identified phenotypes into differences in sgRNA abundance. Recently, several in situ sequencing 15,16 and cell isolation methods [17][18][19][20] were developed which allow microscopes to be used for screening. However, these methods contain non-high throughput steps that limit their scalability.…”
Section: Introductionmentioning
confidence: 99%